Molecular mechanisms of disease‐related human β‐actin mutations p.R183W and p.E364K. (13th October 2014) - Hundt, Nikolas; Preller, Matthias; Swolski, Olga; Ang, Angella M.; Mannherz, Hans G.; Manstein, Dietmar J.; Müller, Mirco
<x xml:space="preserve">Abstract</x> Cytoplasmic β‐actin supports fundamental cellular processes in healthy and diseased cells including cell adhesion, migration, cytokinesis and maintenance of cell polarity. Mutations in ACTB, the gene encoding cytoplasmic β‐actin, lead to severe disorders with a broad range of symptoms. The two dominant heterozygous gain‐of‐function β‐actin mutations p.R183W and p.E364K were identified in patients with developmental malformations, deafness and juvenile‐onset dystonia (p.R183W) and neutrophil dysfunction (p.E364K). Here, we report the recombinant production and functional characterization of the two mutant proteins. Arg183 is located near the nucleotide‐binding pocket of actin. Our results from biochemical studies and molecular dynamics simulations show that replacement by a tryptophan residue at position 183 establishes an unusual stacking interaction with Tyr69 that perturbs nucleotide release from actin monomers and polymerization behavior by inducing a closed state conformation. The replacement of Glu364 by a lysine residue appears to act as an allosteric trigger event leading to the preferred formation of the closed state. Thus, our approach indicates that both mutations affect interdomain mobility and nucleotide interactions as a basis for the formation of disease phenotypes in patients.